2022
DOI: 10.1371/journal.pone.0265288
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of respiratory viruses among paediatric patients in acute respiratory illnesses in Malaysia

Abstract: Objectives Acute respiratory infections (ARIs) are one of the leading causes of childhood morbidity and mortality worldwide. However, there is limited surveillance data on the epidemiological burden of respiratory pathogens in tropical countries like Malaysia. This study aims to estimate the prevalence of respiratory pathogens causing ARIs among children aged <18 years old in Malaysia and their epidemiological characteristics. Methods Nasopharyngeal swab specimens received at 12 laboratories located in di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
3
3
0
Order By: Relevance
“…Thus, a larger sample size is required for future studies to comparatively demonstrate the effect of COVID-19 on RSV seasonality. Nevertheless, we agree with the findings from our local colleagues Low et al who also reported an increase of 517.4% in RSV cases from 2015 to 2019 [13].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Thus, a larger sample size is required for future studies to comparatively demonstrate the effect of COVID-19 on RSV seasonality. Nevertheless, we agree with the findings from our local colleagues Low et al who also reported an increase of 517.4% in RSV cases from 2015 to 2019 [13].…”
Section: Discussionsupporting
confidence: 94%
“…According to a health report by the Malaysian Ministry of Health in 2020, disease in the respiratory system was ranked as one of the top three major causes of hospitalization, with 9.01% and 11.55% of admissions in public and private hospitals, respectively [19]. Similarly to many other studies, our result also highlighted that children younger than two years are more susceptible to RSV infection, and the positive detection rate decreased tremendously as the age of children increased [12,13]. This can be partly explained by the diminishing role of natural passive maternal immunity within months after birth, posing a higher risk to infants aged younger than six months.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The World Health Organization (WHO) global influenza surveillance standards define the surveillance case definitions for influenza-like illness (ILI) as an acute respiratory infection with fever ³38°C and cough, with onset within the last 10 days (WHO). The most commonly diagnosed flu-like viruses include: parainfluenza 1-4 (PIV-1, PIV-2, PIV-3, PIV-4), human respiratory syncytial virus (RSV), human corona virus (HCoV), human rhinovirus (RV), human adenovirus (ADV), and human metapneumovirus (hMPV) [5,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%